Adverse drug reactions as the reason for visiting an emergency department (2008)
Objective: Determining the prevalence of adverse drug reactions (ADR) as the reason for visiting an emergency department. Methods: The study took place at the Luis Carlos Galán Sarmiento ESE's Emergency Department's Central Outpatient Centre in Bogotá. It was carried out from September 20 th to October 2nd 2004. ADR were identified by an evaluator who reviewed all clinical histories, noting when physicians had indicated that an ADR had occurred. The patients were contacted. Two people evaluated causality, the degree of preventability and the mechanism producing the ADR. Results: 45 ADR were recorded in 1,395 visits made during a two-week period (2.8% of the consultations). Modified spontaneous report detected 26.7% ADR identified by active search. 73.3% of all identified ADR occurred in females, 64.9% in people older than 60. 48.9% were non-preventable, 22.2% preventable and 28.9% were unclassifiable. Conclusions: ADR represent a significant proportion of the reasons for outpatient consultation; the modified spontaneous report system detected a large percentage of ADR. There were no statistically significant differences between gender and ADR frequency. ADR occurred more frequently in elderly patients. Around 2 out of each 10 ADR could have been prevented.